The exacerbation of the phenomenon of migration and terrorism and its repercussions on the European Union - Assistant Professor Dr. Ibrahim Hardan Matar; Researcher Ghufran Abdul Karim Tawfiq (The college of law and political science journal, 2023)
- The exacerbation of the phenomenon of migration and terrorism and its repercussions on the European Union